2020
DOI: 10.22331/q-2020-08-28-313
|View full text |Cite
|
Sign up to set email alerts
|

Weak approximate unitary designs and applications to quantum encryption

Abstract: Unitary t-designs are the bread and butter of quantum information theory and beyond. An important issue in practice is that of efficiently constructing good approximations of such unitary t-designs. Building on results by Aubrun (Comm. Math. Phys. 2009), we prove that sampling dtpoly(t,log⁡d,1/ϵ) unitaries from an exact t-design provides with positive probability an ϵ-approximate t-design, if the error is measured in one-to-one norm. As an application, we give a randomized construction of a quantum encryption … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…However, it has been shown that -approximate unitary t-designs on n qubits can be efficiently constructed with local random circuits that are polynomial in n, t and log(1/ ) [BHH16]. In this work, we use the construction of an -approximate unitary t-design from [LM20], where they prove an upper bound for when the unitaries are sampled from an exact tdesign (Theorem 3.1). They show that when at most C(td) t (t log d) 6 / 2 unitaries are sampled from a t-design for some constant C, then this is an -approximate unitary t-design with probability at least 1 2 .…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations

Quantum Private Broadcasting

Broadbent,
González-Guillén,
Schuknecht
2021
Preprint
“…However, it has been shown that -approximate unitary t-designs on n qubits can be efficiently constructed with local random circuits that are polynomial in n, t and log(1/ ) [BHH16]. In this work, we use the construction of an -approximate unitary t-design from [LM20], where they prove an upper bound for when the unitaries are sampled from an exact tdesign (Theorem 3.1). They show that when at most C(td) t (t log d) 6 / 2 unitaries are sampled from a t-design for some constant C, then this is an -approximate unitary t-design with probability at least 1 2 .…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The proof of Theorem 6.6 follows similarly to [LM20], with altered bounds due to ρ being in the symmetric subspace. To see this, we need the following result based from [Aub09] Lemma 5, now adjusted so that ρ ∈ D(Sym(d t )) and U ⊗t i is being applied instead of simply U i .…”
Section: Symmetric Unitary T-designsmentioning
confidence: 99%
See 3 more Smart Citations

Quantum Private Broadcasting

Broadbent,
González-Guillén,
Schuknecht
2021
Preprint